ปัจจัยที่มีความสัมพันธ์กับระยะเวลาคาท่อช่วยหายใจหลังผ่าตัดหัวใจ - จงเจริญกำโชค, อัจฉรา; กิจจานนท์, นฤมล (Nursing Research and Innovation Journal, 2013)
บทคัดย่อ การวิจัยสำรวจเชิงบรรยายนี้มีวัตถุประสงค์ของการวิจัยเพื่อศึกษาปัจจัยที่มีความสัมพันธ์กับระยะเวลาคาท่อช่วยหายใจ โดยการศึกษาย้อนหลังจากเวชระเบียนประวัติการรักษาของผู้ป่วย ที่ได้รับการผ่าตัดหัวใจ จำนวน 153 ราย ในโรงพยาบาลมหาวิทยาลัยของรัฐบาล ระยะเวลา ตั้งแต่เดือน ธันวาคม พ.ศ. 2549- พฤศจิกายน พ.ศ. 2550 โดยแบบรวบรวมข้อมูลที่ได้สร้างเพื่อการศึกษานี้ วิเคราะห์ข้อมูลโดยใช้สถิติบรรยาย Spearman’s Rho, Mann-Whitney U test, และ Kruskal-Wallis test ข้อมูลการรักษาพยาบาลของผู้ป่วยที่ได้รับการผ่าตัดหัวใจนำมาศึกษา จำนวน 149 ราย การผ่าตัดหัวใจประกอบด้วยการผ่าตัดตบแต่งหรือเปลี่ยนลิ้นหัวใจ การผ่าตัดหลอดเลือดหัวใจ และการผ่าตัดแก้ไขความผิดปกติของหัวใจแต่กำเนิด กลุ่มตัวอย่างมีอายุเฉลี่ย 52.42 ± 15.35 ปี (15-91 ปี) มีระยะเวลาคาท่อช่วยหายใจ 1- 143 ชั่วโมง เฉลี่ย 26.19 ± 21.67 ชั่วโมง ค่ามัธยฐาน (Median) 19 ชั่วโมง ความถี่มากที่สุด (mode) คือ 18 ชั่วโมง ปัจจัยที่มีความสัมพันธ์ กับระยะเวลา คาท่อช่วยหายใจหลังผ่าตัดหัวใจ ได้แก่ จำนวนเลือดที่ใช้ในห้องผ่าตัด การมาผ่าตัดแบบฉุกเฉิน และระยะเวลาคาสายระบายทรวงอก และพบว่าระยะเวลาคาท่อช่วยหายใจมีความสัมพันธ์กับระยะเวลาในไอซียู และระยะเวลาในโรงพยาบาลหลังผ่าตัด ผลการศึกษาครั้งนี้สามารถใช้เป็นข้อมูล พื้นฐานสำหรับพยาบาลและบุคลากรทางการแพทย์ในการพัฒนาคุณภาพการรักษาพยาบาลเพื่อ เฝ้าระวังปัจจัยที่สัมพันธ์กับระยะเวลาในการคาท่อช่วยหายใจในผู้ป่วยที่ได้รับการผ่าตัดหัวใจ คำสำคัญ: ระยะเวลาคาท่อช่วยหายใจ การผ่าตัดหัวใจ จำนวนเลือดที่ใช้ในห้องผ่าตัด การมาผ่าตัดแบบฉุกเฉิน ระยะเวลาคาสายระบายทรวงอก Abstract The objective of this descriptive survey research was to examine factors influencing intubation duration in patients who underwent heart surgery. The medical records of 153 heart surgery patients were reviewed retrospectively during December 2006-November 2007. The information had been recorded on the survey tool that was developed for this study. Data analysis was done using descriptive statistics, Spearman’s Rho, Mann-Whitney U test, and Kruskal-Wallis test. Medical records of 149 heart surgery patients were recruited in this study. The heart surgery included coronary artery bypass surgery, valvuloplasty or valve replacement, and congenital heart disease correction surgery. The mean age of the patients was 52.35 ± 15.38 years (range 15-91 years). The range of intubation duration was 1-143 hours. The average intubation duration was 26.19 ± 21.67 hours. The median intubation duration was 19 hours and mode of intubation duration was 18 hours. The significant factors influencing the intubation duration in heart surgery patients included the amount of blood used in the operating room, emergency operation, and chest drain dwelling duration. The intubation duration was associated with the length of stay in the intensive care unit and the length of stay in hospital after surgery. Findings from this study provide basic information for nurses and the health care team to improve quality of care and reduce factors influencing intubation duration preoperatively in patients with heart surgery. Keywords: Intubation duration, Heart surgery, Amount of blood used, Emergency operation, Chest drain dwelling duration